(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The process of writing in a second language is a complex cognitive and linguistic activity that requires learners to simultaneously manage content, language form, organization, and communicative purpose. Unlike first language writing, second language (L2) writing is influenced by limited linguistic competence, cross-linguistic transfer, and psychological factors such as anxiety and motivation. This article aims to analyze the process of second language writing by examining its main stages, cognitive demands, and the challenges faced by learners in academic contexts. Special attention is given to the role of planning, drafting, revising, and feedback in improving writing proficiency. The study also highlights the importance of pedagogical strategies that support learners during the writing process and promote the development of effective academic writing skills at the university level.